Impactos de gastos estruturais e sociais na pobreza do Brasil - Cidrão, Silvia Andrea Soares Beserra (2017)
This work aims to analyze the impact of socias spending and infrastructure in the relevant sectors of the economy, on poverty. The infrastructure is considered by the so-called institutional economy as the pillar for socio-economic activities. Spendings on education and social assistance are imprescindivies for a good quality of life and development of a nation. Here, we study the impact of these spendings on poverty reduction, controlled by other determinants such as income inequality, and especially: a Dummy variable that aims to capture the location of the state in the Northeast region as a factor for poverty explanation. The sample period extends from 2009 to 2013, a model for dynamic panel data, estimated by the method of generalized least squares (EGLS). It was found evidence that there is a significant relationship between public investment in infrastructure and social spendings on the reduction of poverty.